Distal ileum perforation caused by a fish bone: A case report - Lozada Martinez, Ivan David (2019)
We present a case of distal ileum perforation after the ingestion of a fish bone. This case report includes the symptomatology, studies conducted for reaching a concise diagnosis, abdominal ultrasound results, and description of the operative technique. In addition, a discussion of the topic and information gathered from the literature is carried out.